Removal of Heavy Metal Ions from Wastewater using Nanotechnology: A Review - Amritpal Singh S; Sandhya Bharambhe; Pushpinder G. Bhatia (International Journal of Scientific Research in Chemistry, 2025)
Water pollution refers to the contamination of water sources by substances which make the water unusable for drinking, cooking, cleaning, swimming, and other activities. Pollutants include chemicals, trash, bacteria, and parasites. All these forms of pollution, directly or indirectly, make their way to water. Millions of people have lost their lives due to consumption of contaminated water. Due to rapid increase in population, development of new industries, there has been increase in water contamination. Major sources of water contaminants are in the form of organic pollutants, inorganic & biological pollutants. Inorganic pollutants include heavy metals like Pb, Cr, Cd, As, Cr, Hg etc. These heavy metals are harmful if consumed above their safety limits. Heavy metal-based industries have grown rapidly, and this has resulted in serious environmental problems with local dumping and wastewater from these industries. Nanotechnology is a rapidly expanding science with noteworthy outcomes in practically all areas of life. In recent years, active researchers are mostly interested in nanomaterials because of their distinctive characteristics, such as excellent reactivity and better catalysis. This review article, firstly, emphasizes on the methods employed for removal of Heavy Metal Ions from wastewater. Also, different types of nanomaterials used in the removal of Heavy Metal Ions & their future prospects are discussed further.
Keywords: Nanomaterial’s; Heavy Metal Ions; Contamination; Magnetic nanoparticles; Wastewater; Adsorption